GIS-Based Vulnerability Analysis for Sustainable Fish Drying Cottage Industry in Southern Province, Sri Lanka (International Journal of Built Environment and Sustainability, 2022)
Dried fish manufacturing is a famous cottage industry in Sri Lanka. Due to various natural and manmade reasons, their locations are not set up in sustainable ways. As a result, industry locations have become more vulnerable. Therefore, hurdles are there to sustainably expanding this cottage industry. So, the industry's novelty and the enormous number of issues experienced have yet to be discovered or solved via research study. Therefore, the current study intends to conduct GIS-based vulnerability analysis of the fish drying cottage industry by identifying the socioeconomic, environmental, and industry-related backgrounds of existing manufacturers and the industry, challenges faced by manufacturers, and vulnerable sites in the village using geo-spatial analysis. The case study focuses on Kudawella of Tangalle local authority, in the southern province of Sri Lanka. Qualitative analysis was used to identify the existing situation using a structured questionnaire survey and descriptive analysis was performed on the obtained information. The constraints were revealed by a content analysis of qualitative data acquired from a judgemental sample via semi-structured and unstructured interviews. Furthermore, the relative positions of the cottages were determined using OpenStreet Map and the absolute coordinates of a sample of 27 cottages gathered using GPS. A Weighted Overlay Analysis was performed using Arc Map 10.8 to create a Vulnerability Index Map to identify vulnerable locations for the industry while taking nine socioeconomic and environmental parameters.  The outcome indicated four categories of vulnerability: severe, moderately severe, moderate, and low vulnerability, with 4.13% of the village falling into the severely susceptible category. The index map assists relevant authoritative organisations in making industrial decisions to attain sustainability based on the amount of risk and underlines the importance of institutional and individual decision-making systems
Keywords: Fish Drying Cottage Industry, GIS, Geospatial Analysis, Vulnerability Analysis; Vulnerability Index Map